RELEVANCE CAUSA PARADIGMATIC OF LEGAL POSITIVISM : A Study and New Interpretation Paradigmatic Law - Puspitasari, Deny; Kusuma Putra, Rengga (JIL : Journal of Indonesian Law, 2024)
Law, as a science, is philosophical series of reasoning towards comprehensive rules, while law as an instrument is set of rules that regulate behavior is very profane and tends to have a one-way perspective. That beside das sein and das sollen sometimes be through contra productive assumptions, implementation, perceptions and expectations, especially those related the reasons behind legal determination. Interesting one thing is positivism paradigm. Where reason constructs values based solely on legal postulates, ignoring the context, forming reasoning, assumptions, perceptions and simbiota fact that encourage legal violations. The aims of this research is to examine how the construction, logical implementation, and whether there are logical contradictions of the positivism paradigm in law. As a result, this paradigm is aimed forming a perception of the text as a fact of knowledge. Implementably, construction of positivism paradigm cannot be separated from the construction of its constituents, that philosophy which includes what positivism is (ontology), how positivism is formed or obtained (epistemology) and why positivism was born (actiology) and logical contradictions in the positivism paradigm are influenced by differences in form, both of aspects elemental construction, basic thoughts, basic perceptions, basic assumptions, basic interpretations, factual basics in the social domain which form logical reasoning based on factual factors in society.